2014
DOI: 10.3390/md12052422
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Marine Bacillus for Use as Livestock Probiotics

Abstract: Six antimicrobial-producing seaweed-derived Bacillus strains were evaluated in vitro as animal probiotics, in comparison to two Bacillus from an EU-authorized animal probiotic product. Antimicrobial activity was demonstrated on solid media against porcine Salmonella and E. coli. The marine isolates were most active against the latter, had better activity than the commercial probiotics and Bacillus pumilus WIT 588 also reduced E. coli counts in broth. All of the marine Bacillus tolerated physiological concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 44 publications
5
27
1
Order By: Relevance
“…The isolates CM2, CM4, CM11, CM35 and CF2 showed a 100% decrease in cell viability when exposed to simulated gastric conditions at 37∞C for 30 min, while CM40 and PF7 showed 25.84% and 22.33% survival, respectively (Table 2). This result was in agreement with that of a previous study, which showed that the vegetative cells of almost all marine-derived Bacillus, except for B. pumilus WIT 584 and B. licheniformis WIT 586, were undetectable after only 30 min of exposure to simulated gastric juice (pH 2.2) (Prieto et al, 2014). However, our findings were not consistent with those observed for the vegetative cells of B. polyfermenticus CJ6, which exhibited a very high survival rate (60-96%) after acid treatment for up to 2 h (Jung et al, 2012).…”
Section: Acid and Bile Salt Tolerance Of Vegetative Cells And Sporessupporting
confidence: 93%
See 2 more Smart Citations
“…The isolates CM2, CM4, CM11, CM35 and CF2 showed a 100% decrease in cell viability when exposed to simulated gastric conditions at 37∞C for 30 min, while CM40 and PF7 showed 25.84% and 22.33% survival, respectively (Table 2). This result was in agreement with that of a previous study, which showed that the vegetative cells of almost all marine-derived Bacillus, except for B. pumilus WIT 584 and B. licheniformis WIT 586, were undetectable after only 30 min of exposure to simulated gastric juice (pH 2.2) (Prieto et al, 2014). However, our findings were not consistent with those observed for the vegetative cells of B. polyfermenticus CJ6, which exhibited a very high survival rate (60-96%) after acid treatment for up to 2 h (Jung et al, 2012).…”
Section: Acid and Bile Salt Tolerance Of Vegetative Cells And Sporessupporting
confidence: 93%
“…Our isolates showed an adherence ability to HT-29 which was higher than those reported (0.001-0.06%) for marine-derived Bacillus (Prieto et al, 2014). The spores of CM35 and PF7 displayed the strongest adherence to HT-29 and Caco-2 cells at 1.73% and 3.18%, respectively.…”
Section: Safety Evaluation Of Bacillus Isolatescontrasting
confidence: 67%
See 1 more Smart Citation
“…It has previously been suggested that biofilm formation of Bacilli is a prerequisite for prolonged persistence in the intestine (Tam et al 2006;Prieto et al 2014) and we therefore tested for the ability to produce biofilm specifically testing for pellicle formation in order to include the biofilm formation ability in our assessment of the suitability of the strains. Using this approach, all selected strains with the exception of B. subtilis strain 5036 were able to produce robust biofilms ( Supplementary Fig.…”
Section: Sporulation and Biofilm Formationmentioning
confidence: 99%
“…They participate in fermentation of marine foods (Dewapriya and Kim, 2014;Tanasupawat and Visessanguan, 2014), can produce various compounds to be used as natural food additives and/or functional ingredients and can also be exploited as probiotics for use in human or productive animals diet Dewapriya and Kim, 2014;Prieto et al, 2014).…”
Section: Food Related Compounds From Marine Environmentmentioning
confidence: 99%